Molecular Mechanisms of AhpC in Resistance to Oxidative Stress in Burkholderia thailandensis - Zhang, Bing; Gu, Huawei; Yang, Yantao; Bai, Haonan; Zhao, Chao; Si, Meiru; Su, Tao; Shen, Xihui (Frontiers in Microbiology, 2019)
Burkholderia thailandensis is a model organism for human pathogens Burkholderia mallei and Burkholderia pseudomallei. The study of B. thailandensis peroxiredoxin is helpful for understanding the survival, pathogenic infection, and antibiotic resistance of its homologous species. Alkyl hydroperoxide reductase subunit C (AhpC) is an important peroxiredoxin involved in oxidative damage defense. Here, we report that BthAhpC exhibits broad specificity for peroxide substrates, including inorganic and organic peroxides and peroxynitrite. AhpC catalyzes the reduction of oxidants using the N-terminal conserved Cys57 as a peroxidatic Cys and the C-terminal conserved Cys171 and Cys173 as resolving Cys. These three conserved Cys residues play critical roles in the catalytic mechanism. AhpD directly interacts with AhpC as an electron donor, and the conserved Cys residues in active site of AhpD are important for AhpC reduction. AhpC is directly repressed by OxyR as shown by identifying the OxyR binding site in the ahpC promoter with a DNA binding assay. This work sheds light on the function of AhpC in the peroxides and peroxynitrite damage response in B. thailandensis and homologous species.